Clinical and Histopathological Evaluation of Odontomes (Medical Forum Monthly, 2020)
Objective: To evaluate the epidemiological features, assess clinical manifestations and histopathological features of odontomes.Study Design: Descriptive case seriesPlace and Duration of Study: This study was conducted at the Department of Oral Pathology, Bacha Khan Medical College Mardan from November 2015 to June 2020.Materials and Methods: Seventeen patients of odontomes were observed. Patients detail medical and dental history, clinical features, radiographic findings on the panoramic radiographs and pathological reports were investigated.Results: 52.9 percent patients were males. Majority of the patients were males with age range 13-17 years. The common chief complaint was bony and soft tissue swelling and 41.2% of the cases the odontomes were associated with unerupted tooth. Anterior maxilla was involved in 35.3% cases followed by posterior mandible which was involved in 17.6% cases. Radiographically 70.6% odontoma appeared as a tooth like structures surrounded by a narrow radiolucent zone and histolopathologically diagnosed as compound odontomes.Conclusion: Odontomes are rare tumors comprising of various dental tissues. The most common form diagnosed is compound odontomes both radiographically and histopathologically. It predominantly involves young males, presenting as swelling in anterior maxilla and most commonly associated with unerupted tooth.